Changes in land use impacted air temperature in Bekasi Regency - Okta Nindita Priambodo; Ade Wachjar; Anugerah Rafi Pratama; Muhammad Sahfitri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Indonesia is experiencing dynamic land change. One area in Indonesia that has experienced high land use change is Central Cikarang District. Landsat 9 image sensing and land cover data from the Ministry ofEnvironment and Forestry show the increased temperature in the Central Cikarang District area since 2004. Based on the NDVI analysis, the residential area has increased, and the area of green vegetation hasdecreased. Analysis of temperature changes using satellite imagery also shows a wider distribution of hot temperatures in the 2004–2022 range. From the two data analyses that were carried out, a regression test was carried out to determine the correlation between air temperature and vegetation density. The results of the regression test obtained an R2 value of 7.2%. It is also known that the value of the regression coefficient is negative, which means that the correlation of the two data is inversely proportional. So this research analyzes changes in land cover to changes in temperature.